2016
DOI: 10.2147/prom.s102647
|View full text |Cite
|
Sign up to set email alerts
|

Cultural adaptation: translatability assessment and linguistic validation of the patient-reported outcome instrument for irritable bowel syndrome with diarrhea

Abstract: Background and objectiveFollowing a 2009 US Food and Drug Administration guidance, a new patient-reported outcome (PRO) instrument was developed to support end points in multinational clinical trials assessing irritable bowel syndrome with diarrhea (IBS-D) symptom severity. Our objective was to assess the translatability of the IBS-D PRO instrument into ten languages, and subsequently perform a cultural adaptation/linguistic validation of the questionnaire into Japanese and US Spanish.Materials and methodsTran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It has undergone both qualitative assessments of content validity and quantitative assessments of its psychometric properties. 5 7 The pen-and-paper version of the instrument is shown in Figures 1 and 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has undergone both qualitative assessments of content validity and quantitative assessments of its psychometric properties. 5 7 The pen-and-paper version of the instrument is shown in Figures 1 and 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The IBS-D PRO instrument, which comprises two questionnaires – the IBS-D Daily Symptom Diary and the IBS-D Symptom Event Log (Astellas Pharma Global Development, Inc., Northbrook, IL) was developed for use within clinical trials and real-world settings; 4 its ability to be translated into ten languages has been confirmed. 5 The primary goal of this study was to support the migration of the IBS-D PRO instrument from its pen-and-paper-based version to an electronic mobile version by testing the conceptual equivalence of the two formats and the usability of the mobile application for subjects with IBS-D.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐English speakers may not perceive the nuances in English words, and some regional terms may not have equivalent English words 14 . The Rome Foundation Working Team has suggested that culturally adapted questionnaires or other instruments would be of great help in describing a true picture of FGIDs in different cultural regions 14,15 . Studies have indicated diagnostic dilemmas in Asian patients with irritable bowel syndrome (IBS) derived from different cultural perceptions of symptoms 16‐18 .…”
Section: Introductionmentioning
confidence: 99%
“…14 The Rome Foundation Working Team has suggested that culturally adapted questionnaires or other instruments would be of great help in describing a true picture of FGIDs in different cultural regions. 14,15 Studies have indicated diagnostic dilemmas in Asian patients with irritable bowel syndrome (IBS) derived from different cultural perceptions of symptoms. [16][17][18] For instance, a single Mandarin word or phrase could contain one or several symptom patterns.…”
mentioning
confidence: 99%
“…A PubMed search using “translatability,” “assessment,” “review,” or “assurance” as key words retrieved only eight papers [ 10 17 ]. In seven of them [ 11 17 ], it is assumed that TA offers original and qualitative knowledge on the cross-cultural relevance of concepts, a type of information not provided by psychometric results. Only one paper out of the eight retrieved (Conway et al [ 10 ]) has documented its value and how it is performed.…”
Section: Introductionmentioning
confidence: 99%